“Apertura Comercial y desigualdad en los países de América del Sur: periodo 1980-2015 ” - Abad Ramón., Robinson Ivan (2021)
Inequality is a social problem that affects the whole world, it is also one of the main economic and social problems that countries face globally.However, according to ECLAC (2018), Latin America is one of the most unequal regions of the world. world. That is why the objective of the research is to determine the relationship between international trade and inequality for the countries of South America, using panel econometric techniques, for the period 1980-2015. Data were obtained from the World Bank (2018). In addition to this, the Hausman Test (1978) was applied to choose between fixed or random models. Then the Wooldridge test (2002) was used to detect autocorrelation and the Wald test to detect heteroskedasticity. To estimate the causal relationship, the Granger-type causality test proposed by Dumitrescu and Hurlin (2012) was applied. It was possible to show that trade openness has a positive and significant effect on inequality, so that an increase in trade openness causes a decrease in inequality, that is, as these countries receive a greater amount of foreign capital, they will decrease the inequality, for this it is necessary to promote the creation of production-oriented companies and provide training in micro-enterprises to future entrepreneurs so that people can forge their own employment opportunities.